Stature of Chest Rontgenography in Extra Pulmonary Tuberculosis; A Prospective Observation at Tertiary Care Center - Devraj , Mayur Vikram (Research Highlights in Disease and Health Research Vol. 5, 2023)
Introduction: One out of every five cases of TB turned up as extra pulmonary tuberculosis(EPTB).In 2019 around 16% cases of EPTB contributed to the 7.5 million incident cases of tuberculosis in worldwide. Material & Methods: This was prospective observational study. The confirmed cases of EPTB of all age group were included in study. Clinical history, examination and investigations were done. We compiled the findings of chest roentgenogram in these confirmed cases of EPTB. We classify the findings according to the pattern of involvement as I) Normal II) Parenchymal (Infiltrates / cavitation) iii) Hilar prominence (Unilateral or Bilateral) IV) Pleural. Results: Total 96 cases of EPTB were included in the study.27 (28.12%) were diabetic, 21 (21.87%) were Hypertensive and 08 (8.33%) had hypothyroidism. Out of 96 cases majority of cases were of cervical lymphadenopathy 41 (41.70%), 22 (22.90%) were Spine TB and 13 (13.54%) were Genitourinary TB. Gastrointestinal cases were 11 (11.45%) while 09 (9.37%) were Meningeal TB. Total 27 (28.12%) cases had Chest radiograph abnormalities. Among those 27 subjects 18 (18.75%) had parenchymal lesions, 6 (6.25%) had Hilar Lymphadenopathy, 3 (3.12%) had pleural and 69(71%) had normal chest x ray. Conclusion: Our objective was to emphasize the chest Rontgenography in EPTB which point out pulmonary involvement. We found significant cases of EPTB had abnormal changes in chest imaging suggest lung involvement which can be infectious in community. We endorse the statement of national guideline for necessity of chest imaging in EPTB.